The metastatic pattern of intestinal and diffuse type gastric carcinoma – A Dutch national cohort study. (December 2020) - Koemans, W.J.; Luijten, J.C.H.B.M; van der Kaaij, R.T.; Grootscholten, C.; Snaebjornsson, P.; Verhoeven, R.H.A.; van Sandick, J.W.
Highlights: Intestinal and diffuse type gastric carcinoma have different metastatic patterns. The most common site of metastases of the intestinal type is the liver. The most common site of metastases of the diffuse type is the peritoneum. Patients with metastatic gastric cancer of the diffuse type have the worst survival. Abstract: Introduction: The Lauren classification of gastric adenocarcinoma describes three histological subtypes, the intestinal, the diffuse and the mixed type carcinoma. The metastatic pattern of gastric adenocarcinoma by histological subtype has not been studied. Methods: Gastric adenocarcinoma patients with metastatic disease at the time of diagnosis between 1999 and 2017 were identified through the Netherlands Cancer Registry. The Lauren classification was determined based on pathology reports archived in the Dutch Pathology Registry and was linked to individual cases in the Netherlands Cancer Registry. Results: Among 8 231 newly diagnosed, metastatic and evaluable gastric adenocarcinoma patients, 57 % had an intestinal type carcinoma, 38 % patients had a diffuse type carcinoma and 5 % had a mixed type carcinoma. Intestinal type carcinomas more often metastasized to the liver (57 % versus 21 %, p < 0.0001) and lungs (13 % versus 7 %, p < 0.0001), whereas diffuse type carcinomas more often metastasized to the peritoneum (58 % versus 29 %, p < 0.0001) and bones (9 % versus 6 %, p < 0.0001). Patients with a diffuse type carcinoma had a worse survival perspective regardless of the number or the location of the metastases. Conclusion: In this national cohort study, metastatic gastric adenocarcinoma of the intestinal type had a predilection for the liver and that of the diffuse type for the peritoneum.